2003
DOI: 10.1046/j.1439-0388.2003.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of somatic cell count in dairy sheep considering the type of mammary pathogen effect

Abstract: Summary Genetic parameters for somatic cell count (SCC) from half‐udder milk were estimated from 4692 monthly test‐day records from each half‐udder of 1337 Churra ewes belonging to seven dairy flocks. The total number of observations was 9348. Variance and co‐variance genetic components were estimated using a multitrait repeatability animal model. The log SCC of the right and left half‐udders were considered as two dependant variables in the model. The species of organisms causing intramammary infection were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Subclinical mastitis is generally diagnosed by an increase in somatic cell counts (SCC) in the milk of cows and ewes, although in goats the predictive value of SCC is less established (Bergonier et al, 2003). SCC may also be used to help select for increased resistance to mastitis though recent estimates of heritability for SCC are generally low ranging from 0.10 to 0.20 (Mrode and Swanson, 1996;El-Saied et al, 1999;Barillet et al, 2001;Rupp et al, 2003;Serrano et al, 2003;Gonzalo et al, 2003;Legarra and Ugarte, 2005;Bishop and Morris, 2007). The review by Mrode and Swanson (1996) summarized many genetic estimates, concluding that the heritability of mastitis incidence in dairy cattle is low (∼ 0.04), as also is the heritability of SCC (0.11 ± 0.04), but the genetic correlation between the two is high at ∼0.70.…”
Section: Bacterial Diseasesmentioning
confidence: 99%
“…Subclinical mastitis is generally diagnosed by an increase in somatic cell counts (SCC) in the milk of cows and ewes, although in goats the predictive value of SCC is less established (Bergonier et al, 2003). SCC may also be used to help select for increased resistance to mastitis though recent estimates of heritability for SCC are generally low ranging from 0.10 to 0.20 (Mrode and Swanson, 1996;El-Saied et al, 1999;Barillet et al, 2001;Rupp et al, 2003;Serrano et al, 2003;Gonzalo et al, 2003;Legarra and Ugarte, 2005;Bishop and Morris, 2007). The review by Mrode and Swanson (1996) summarized many genetic estimates, concluding that the heritability of mastitis incidence in dairy cattle is low (∼ 0.04), as also is the heritability of SCC (0.11 ± 0.04), but the genetic correlation between the two is high at ∼0.70.…”
Section: Bacterial Diseasesmentioning
confidence: 99%
“…As a consequence, correlated traits have been suggested to increase the efficiency of selection for mastitis resistance. In particular, SCC has been promoted as an indirect method of predicting mammary infections (Boettcher, 2005) and as a selection criterion to improve mastitis resistance (Gonzalo et al, 2003). It has been indeed demonstrated that mastitis causes an increase in SCC in small ruminants (Leitner et al, 2004;Sanchez et al, 1999;Zeng et al, 1997) (e.g., Heringstad et al, 2006;Olde Riekerink et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In sheep a heritability estimate of 0.09 for infection status assessed by bacteriological analyses was reported by Riggio et al [ 24 ] and Tolone et al [ 25 ] in the Valle del Belice breed using a threshold animal model assuming a probit link function. Gonzalo et al [ 39 ] estimated genetic parameters of SCC in Churra sheep considering the type of mammary pathogen using a multitrait repeatability animal model. They reported that the effect related to the type of pathogen accounted for 32.5 % of the total variance in SCC, a value similar to that obtained for the residual effect (34.9 %), indicating a high relative importance of the type of pathogen in the decomposition of the variance for SCC.…”
Section: Discussionmentioning
confidence: 99%